2021
DOI: 10.1038/s41467-021-25076-7
|View full text |Cite
|
Sign up to set email alerts
|

Structures of a deAMPylation complex rationalise the switch between antagonistic catalytic activities of FICD

Abstract: The endoplasmic reticulum (ER) Hsp70 chaperone BiP is regulated by AMPylation, a reversible inactivating post-translational modification. Both BiP AMPylation and deAMPylation are catalysed by a single ER-localised enzyme, FICD. Here we present crystallographic and solution structures of a deAMPylation Michaelis complex formed between mammalian AMPylated BiP and FICD. The latter, via its tetratricopeptide repeat domain, binds a surface that is specific to ATP-state Hsp70 chaperones, explaining the exquisite sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 71 publications
0
35
0
6
Order By: Relevance
“…Solubilised His-FICD adopted a single oligomeric state as judged by SEC analysis ( Figure 5 B), as is the case for N-terminally truncated FICD, which forms a highly stable homodimer in the solution and in all published structures, e.g. [ 10 , 11 , 12 ]. To assess the oligomeric state of His-FICD experimentally, we employed native mass spectrometry, but were unfortunately not able to detect the protein by this method (Drs.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Solubilised His-FICD adopted a single oligomeric state as judged by SEC analysis ( Figure 5 B), as is the case for N-terminally truncated FICD, which forms a highly stable homodimer in the solution and in all published structures, e.g. [ 10 , 11 , 12 ]. To assess the oligomeric state of His-FICD experimentally, we employed native mass spectrometry, but were unfortunately not able to detect the protein by this method (Drs.…”
Section: Discussionmentioning
confidence: 70%
“…( A ) FICD is comprised of a short N-terminal cytosolic tail, a transmembrane domain (TM; dark grey), two tetratricopeptide repeats (TPR; turquoise), a linker (yellow), and the catalytic Fic domain (FIC; blue). The segment for which crystal structures have been solved (approximately residues 102 to 445 depending on the particular study) is indicated [ 10 , 11 , 12 , 22 ]. The numbers denote residue positions that mark the boundaries of key regions in the structure of FICD.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…This biochemical feature is consistent with earlier observations that levels of modified (AMPylated) BiP are regulated physiologically: decreasing with mounting ER stress and increasing with stress resolution (Hendershot et al, 1988; Laitusis et al, 1999). This balancing act is critically-dependent on FICD (Casey et al, 2017; Preissler et al, 2017a) and arises from fine tuning of the enzyme’s active site to reciprocally regulate its two antagonistic functions (Perera et al, 2021; Perera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%